Studi Linguistik Nama Brand Berbahasa Jawa pada Produk Teh - Adinatha, Giovani; Hemas, Saras Fairuz (Sutasoma : Jurnal Sastra Jawa, 2021)
This research focused on tea brand names derived from Javanese language. The objective is to describe the name’s structure andmeaning. Descriptive-qualitative approach was used in this research with data from two online marketplace, Shopee andTokopedia, focusing only on tea brand names derived from Javanese language. The data were chosen by using purposive samplingtechnique and recorded by taking screenshots Shopee and Tokopedia. The data were analyzed by content analysis technique. Datavalidity was retrieved by researcher’s triangulation and persistency. The triangulation was conducted by analysing data, done bymore than one researcher. After they were analyzed, data were presented both formally and informally. Results from this researchis that tea brand names derived from Javanese language are consist of words and phrases. Meanings that were found in thosestructure are toponymy descriptors, fictional characters names, iconic names, symbolism names, suggestive names, culture-relatednames, and metaphors. Keywords: brand names; tea products; Javanese language